As relíquias eram a virtus : objetos religiosos e agência no discurso jesuítico das Cartas Ânuas - Província Jesuítica do Paraguai, Séculos XVII e XVIII - Sauter, Juliano (2022)
The Jesuits were important promoters of the cult of relics, the mortal remains of saints revered by Christians since Antiquity. In Província Jesuítica do Paraguai, those artefacts integrated a set of religious objects frequently utilized in practices of healing. Understood as a source of supernatural powers, each relic contained the virtus, a spiritual energy which conserves the vital force of the saint after his death. Historians argue that, in everyday life, the relic was considered to be the saint himself. A purpose of this work is to problematize the historiographic concepts of relic and virtus, proposing an investigation empirically oriented, in the context of southern Spanish America in the eighteenth century. The documentation is composed of predominantly Cartas Ânuas and offers a interdisciplinary approach, making use of anthropology, as for the notion of agency, from Alfred Gell. I approach the relics as mediators of actions and social relations, analysing selected sources and the contents of the speech. Among the results, stands out the reformulation of the concept of virtus.